2H-Indazolo[2,1-b]phthalazine-trione derivatives: Inhibition on some metabolic enzymes and molecular docking studies - Taslimi, Parham; Turkan, Fikret; Turhan, Kadir; Karaman, Halide Sedef; Turgut, Zuhal; Gulcin, Ilhami (WILEY, 2020)
In this study, substituted 2H-indazolo[2,1-b]phthalazine-1,6,11-trione compounds (4a-d) obtained via one-pot three-component condensation reaction of aromatic aldehydes, cyclic 1,3-dione, and phthalhydrazide in ethanol catalyzed by Y(OTf)(3) showed satisfactory inhibitory effects against some important enzymes. Also, these molecules had K-i values in the row of 185.92 +/- 36.03-294.82 +/- 50.76 nM vs carbonic anhydrase I (CA I), 204.93 +/- 46.90-374.10 +/- 83.63 nM against human CA II, 937.16 +/- 205.82-1021.83 +/- 193.66 nM against alpha-glycosidase (alpha-Gly), respectively. For cholinesterase enzymes, the K-i values were found in the range of 47.26 +/- 9.62-72.05 +/- 19.47 nM against acetylcholinesterase (AChE) and 65.03 +/- 9.88-102.83 +/- 25.04 nM against butyrylcholinesterase (BChE), respectively. The inhibition effects of these compounds against enzymes whose name are AChE, BChE, alpha-Gly, hCA I, and hCA II, were compared with control molecules like tacrine, acarbose, and acetazolamide.
Keywords: GLUTATHIONE-S-TRANSFERASE; MULTICOMPONENT REACTIONS; ONE-POT; ACETYLCHOLINESTERASE; BUTYRYLCHOLINESTERASE; LACTOPEROXIDASE; CHOLINESTERASE; PHTHALAZINE; ANTIOXIDANT; CHEMISTRY